Bioactivity of Dodecanoic Acid Extracted from Geitlerinema sp. TRV57 - K, Renugadevi; C, Valli Nachiyar; Zaveri, Moin (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim/Background: Imbalance in oxidant and antioxidant leads to oxidant stress. Increased consumption of exogenous antioxidants helps in neutralizing the oxidant stress and thus protects the cells from oxidant stress. The study focused on the isolation of nutraceutical compound, dodecanoic acid from the marine cyanobacteria Geitlerinema sp. TRV57. Materials and Methods: Various solvents were used to extract the dodecanoic acid. The ability of the dodecanoic acid to neutralize the oxidant was studied by various assay. Results: The GCMS analyses of these extracts revealed the presence of more percentage of saturated fatty acids with dodecanoic acid being the major fraction. These extracts have exhibited appreciable antibacterial, antioxidant and anti-apoptotic activity which can be attributed to the presence of dodecanoic acid. Conclusion: This study indicates Geitlerinema sp TRV57 as a promising agent for the emollient preparation.
Keywords: Fatty acid; Cyanobacteria; Geitlerinema; Dodecanoic acid; Bioactivities